Paint A Portrait: Lived Experience of Parents in the Implementation of Modular Distance Learning - Paco, Daphnee S.; Yazon, Alberto D.; Manaig, Karen A.; Sapin, Sherwin B.; Bandoy, Marcial M. (Universitas Terbuka, 2021)
This study determined the issues and challenges encountered by the parents who facilitated learning at home. This research was a Qualitative-Phenomenological study that utilized the Narrative Form using the responses of the parent-participants in the Key Informant Interview conducted by the researcher. Creswell Method applied in qualitative analysis of these reactions to explore the lived experience of parents who served as Learning Facilitators in Modular Distance Learning. From the responses of the participants in the Key Informant Interview conducted, the researcher was able to extract the following themes that describe their overall ability in painting the portrait of their children: FB: Keeping You Informed,Ã‚Â Education Must Continue, Education Cannot Wait, MDL Finds a Way, Painting a Portrait as Consecrated Responsibility, Race Against Time, and Time Works Wonders.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The researcher was able to draw out issues with implications of the findings on the lived experiences of the parents in painting the portrait of their children as not just a simple task. Their ability to paint the picture and helping their children with their studies were perceived as challenging but added colors in making their future even more meaningful. Ã‚Â Keywords: Paint a Portrait, Modular Distance Learning, Learning Facilitator